Customer perception, altitudes and purchase intention towards organic foods in Kota Kinabalu, Sabah - Ng, Lenny, Yee Wen (2014)
The objective of this study was to examine the consumers' perception of organic food which included organic knowledge, environmental knowledge, price consciousness, health consciousness, food safety and product availability with intention to purchase towards organiC foods In Kota Kinabalu, Sabah. The study also examines the mediating effect of attitude towards organic foods on the relationship between customer perception and purchase intention. 360 respondents were selected for the study in which data was collected from different supermarket and hypermarket in Kota Kinabalu, Sabah using convenient sampling method. Partial least Square (PLS) based Structural Equation Modelling (SEM) was utilized to identify the dimensionality of research variables The results show that organic knowledge, price consciousness and food safety concern have a significant influence on purchase intention. However, other dimension such as environmental concern, health consciousness and food safety concern have Significant effect with attitude towards organiC foods. The mediation analysis results show that attitude towards organic foods mediates the relationships of purchase intention with organic knowledge, environmental concern, health consciousness, food safety concern and product availability. The result shown that food safety appears to be the most Significant factors that affect the purchase Intention of organic food products. It is suggest that organic foods marketers or researchers should focus on food safety in order to increase their customers' consumption of organiC foods. This study also included the limitation of the study and recommendation for future researchers.